أساليب المعاملة الوالدية وأثرها في قلق الامتحان لدى تلاميذ السنة الثالثة ثانوي - غربي, عبد الرحمان (University of Eloued جامعة الوادي, 2023)
ملخص الدراسة : تعالج الدراسة الحالية موضوع أساليب المعاملة الوالدية واثرها في قلق الامتحان لدى تلاميذ السنة الثالثة ثانوي بثانوية ديدي صالح بالزقم ، وذلك خلال الموسم الدراسي 2022/2023 اعتمدت الدراسة على المنهج الوصفي المقارن، وذلك بإستخدام استبيان أساليب المعاملة الوالدية من إعداد الطالبة منصوري فاطمة الزهراء وطبق في دراسة بعنوان: بعض أساليب المعاملة الوالدية وعلاقتها بالتوافق النفسي ، يحتوي على ثلاث محاور ويتضمن 30 عبارة ، اضافة الى مقياس قلق الإمتحان لـ (غربي عبد الناصر- 2015) الذي يحتوي على 33 عبارة مقسمة الى ثلاث ابعاد، وقد تم التأكد من خصائصهما السيكومترية (الصدق، والثبات) على عينة قوامها (43) فردا، تم إختيارهم بطريقة عرضية. تم تطبيق الأدوات في صورتها النهائية على عينة عرضية تتكون من ( 84) فردا، وبعد جمع البيانات وتبويبها، تم معالجتها بالاستعانة بـ (_spss )، وباستخدام اختبار " ت " لدلالة الفروق بين متوسطي مجموعتين مستقلتين، توصلت الدراسة للنتائج التالية:  وجود فروق ذات دلالة احصائية في قلق الامتحان لدى تلاميذ السنة الثالثة ثانوي تبعا لمتغير اساليب المعاملة الوالدية  وجود فروق ذات دلالة إحصائية في جميع ابعاد قلق الامتحان لدى تلاميذ السنة الثالثة ثانوي تبعا لمتغير اساليب المعاملة الوالدية Study summary: The current study addresses the issue of parental treatment methods and their impact on exam anxiety among third-year secondary students at Didi Saleh High School in Zgoum, during the academic season 2022/2023. The study relied on the comparative descriptive approach, using the parental treatment methods questionnaire prepared by the student Mansouri Fatima Al-Zahraa, and applied in a study entitled: Some parental treatment methods and their relationship to psychological adjustment, contains three axes and contains in its initial form 30 phrases, in addition to the test anxiety scale for (Gharbi Abdel Nasser - 2015), which contains 33 phrases divided into three dimensions, and their psychometric characteristics (truth and stability) have been verified on a sample of (43) individuals, who were selected in a cross-sectional way. The tools were applied in their final form to a cross-sample consisting of (84) individuals, and after collecting and tabulating the data, it was processed using (_spss), and using the "T" test to denote the differences between the averages of two independent groups. The study reached the following results:  There are statistically significant differences in test anxiety among third year secondary school students, according to the variable of parental treatment methods.  There are statistically significant differences in all dimensions of exam anxiety among third year secondary school students, according to the variable of parental treatment styles.
دراسة وصفية مقارنة بثانوية ديدي صالح بلدية حساني عبد الكريم
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: اساليب المعاملة الوالدية، Styles de traitement parental, Parental treatment styles; قلق الإمتحان، l'anxiété liée aux examens, exam anxiety